Perkembangan Penyelesaian Sengketa Dalam WTO - Lie, Madeleine (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The World Trade Organization (WTO) is an international organization whose job is to facilitate international trade so that all member countries can compete in an open, fair and orderly manner in accordance with the Most Favored Nation principle stipulated in the 1994 GATT and the Agreement Establishing the WTO. In addition to regulating how international trade should work, the WTO also regulates the settlement of trade disputes between countries / Dispute Settlements. Trade disputes between countries can arise when one member of the WTO, namely a country believes that another WTO member has violated an agreement or commitment that has been made and agreed upon at the WTO. The Handbook on WTO Dispute Settlement explains that having a mechanism to resolve disputes that will occur within the WTO organization can increase the practical value of the commitments made by WTO members who join the WTO.Since 2018, Appellate Body in WTO was rendered non-functional as it lacked a quorum under its rules due to United States of America’s blockade of the appointment of new Appellate Body members, resulting in only 3 members remaining on the Body during 2018. Because of that, Multiparty Interim Appeal Arbitration Arrangement (MPIA) was created in order to replace Appellate Body temporarily.